Pengembangan Modul Elektronik (e-Module) Kimia berbasis Kontekstual sebagai Media Pengayaan pada Materi Kimia Unsur - Salsabila, Nadia; Nurjayadi, Muktiningsih (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This study aims to develop chemistry electronic module (e-Module) based on contextual approach as an enrichment learning media on Chemical Elements for grade 12 science students in SMA/MA. This study uses Research and Development method by Borg and Gall. The instrument that used in this study is questionnaire. The module validated by four experts in content and language, and also three experts in media and graphic. The module also trialed by 19 students of grade 12 science, 33 college students of chemistry education program and 8 chemistry teachers. The ratings that are given by experts, students, and teachers from validation and trial stage can be categorized as good up to very good, so it can be concluded that the module is feasible to be used as a learning media on Chemical Elements for grade 12 science students of SMA/MA. Keywords Chemistry e-Module, contextual approach, learning media